Modified activated regenerated asphalt based on multi-source waste oil and preparation method thereof

CN122978735APending Publication Date: 2026-10-27WUXI JIAOJIAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611238681.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-15
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

实际上,不同来源废弃油脂的极性、黏度、酸值及化学组成差异显著,即便在二元复配体系中,相容性不佳的问题已有所显现;当油脂种类增加至三种及以上时,油分间的相容性矛盾进一步加剧,混合体系易于出现分层、沉淀等不稳定现象,各组分各自的性能优势无法协同发挥

Benefits of technology

1、本申请通过采用PB-b-PGMA-b-PS-b-PDMS四嵌段共聚物作为界面控制剂,其PB嵌段与废食用油、工业导热油相容,降低分层风险。通过四嵌段共聚物中嵌段功能的有序配合,使再生沥青的耐高低温性能、抗水损害性能及抗老化性能获得较为均衡的提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to a modified activated regenerated asphalt based on multi-source waste oil and grease and a preparation method thereof, which comprises aged asphalt and a regenerated material pre-coated on the aged asphalt, the regenerated material comprising the following components in parts by weight: 30-50 parts of waste edible oil, 20-40 parts of industrial heat-conducting oil, 5-15 parts of castor oil, 1-5 parts of an interface control agent, and 0.5-2 parts of a composite stabilizer; the interface control agent is a PB-b-PGMA-b-PS-b-PDMS four-block copolymer. By adopting the PB-b-PGMA-b-PS-b-PDMS four-block copolymer as the interface control agent, the synergistic effect of the PB block being compatible with the non-polar oil phase, the PS block being anchored by pi-pi stacking with bitumen in the aged asphalt, the PGMA block being chemically bonded with the hydroxyl group of the castor oil, and the PDMS block providing a hydrophobic barrier and low-temperature flexibility is utilized, so that the oil and grease components form a stable and uniform pre-coated layer on the surface of the aged asphalt, and the composite stabilizer is combined, thereby achieving the common improvement of the high and low temperature resistance, water damage resistance and aging resistance of the regenerated asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of road engineering materials and waste resource utilization technology, and in particular to a modified activated recycled asphalt based on multi-source waste oil and its preparation method. Background Technology

[0002] During long-term service, asphalt pavements are affected by environmental and traffic factors such as sunlight, air oxidation, and vehicle loads. The lightweight components gradually volatilize or undergo chemical transformation, leading to hardening, brittleness, decreased adhesion, and significant deterioration of road performance. To restore the performance of aged asphalt and realize the resource utilization of waste asphalt mixtures, adding recycling agents to aged asphalt to replenish missing aromatic and saturated components is one of the most commonly used technical methods.

[0003] Waste oils are widely studied as asphalt regenerators or regenerated oil components due to their wide availability, low cost, and certain oil replenishment capacity. Among them, waste edible oil has a relatively balanced comprehensive oil replenishment capacity and can effectively soften aged asphalt. However, its thermo-oxidative stability is poor, and unsaturated bonds are prone to cross-linking or breakage under thermo-oxidative conditions, resulting in insufficient high-temperature deformation resistance and significant degradation of anti-aging properties in regenerated asphalt. Industrial heat transfer oils are discarded after long-term high-temperature cycling. Their components are mainly aromatic hydrocarbons and alkylbenzenes, which have good dissolving ability for asphaltenes in aged asphalt and are advantageous in improving the high-temperature performance of regenerated asphalt. However, the high content of low-boiling-point components in heat transfer oils makes them prone to volatilization loss during the mixing and construction of regenerated asphalt. Low-temperature performance becomes brittle due to the volatilization of light components, and anti-aging ability is limited. Castor oil contains hydroxyl groups in its molecular chain, resulting in a significant plasticizing effect, which is beneficial for improving the low-temperature crack resistance of regenerated asphalt. However, due to its high viscosity and poor fluidity, it is difficult to disperse evenly when directly added to asphalt, and its compatibility with petroleum-based asphalt is limited, resulting in its ineffective improvement of high-temperature shear resistance and water damage resistance. It is evident that each type of waste oil has its own strengths, but each also has different performance limitations. When used alone, they cannot simultaneously meet the comprehensive requirements of recycled asphalt for high-temperature performance, low-temperature performance, water damage resistance, and aging resistance.

[0004] To address the shortcomings of individual oils, some studies have attempted to blend two types of waste oils to achieve complementary performance through "compensating for each other's weaknesses." Examples include mixing industrial heat transfer oil with waste edible oil, or blending castor oil with waste edible oil. However, the full effectiveness of blending depends heavily on the uniform dispersion and stable coexistence of each oil component within the system—a comprehensive performance improvement can only be achieved when each component synergistically leverages its respective advantages. In reality, waste oils from different sources exhibit significant differences in polarity, viscosity, acid value, and chemical composition. Even in binary blending systems, poor compatibility is already apparent. When the number of oil types increases to three or more, the compatibility issues between oil components intensify further, leading to unstable phenomena such as stratification and sedimentation in the mixed system, preventing the synergistic performance advantages of each component. Simultaneously, existing conventional mechanical stirring methods struggle to achieve uniform coating and penetration of multi-component oil phases onto the surface of aged asphalt particles, further hindering the effective reinforcing effect of each component in the blended oil.

[0005] Therefore, how to simultaneously achieve stable and uniform multi-component oil phases, uniform mixing and coating with aged asphalt, and comprehensive durability of service performance when preparing recycled asphalt using multi-source waste oils is a technical problem that urgently needs to be solved in the field of road engineering materials. Summary of the Invention

[0006] In order to improve the high and low temperature resistance, water damage resistance and aging resistance of recycled asphalt, this application provides a modified activated recycled asphalt based on multi-source waste oil and its preparation method.

[0007] Firstly, this application provides a modified activated recycled asphalt based on multi-source waste oils, employing the following technical solution: A modified activated recycled asphalt based on multi-source waste oils includes aged asphalt and recycled material pre-coated on the aged asphalt. The recycled material comprises the following components in parts by weight: 30-50 parts waste edible oil, 20-40 parts industrial heat transfer oil, 5-15 parts castor oil, 1-5 parts interface control agent, and 0.5-2 parts composite stabilizer. The interface control agent is a PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer, wherein PB represents polybutadiene block, PGMA represents polyglycidyl methacrylate block, PS represents polystyrene block, and PDMS represents polydimethylsiloxane block.

[0008] The inventors used a PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer as an interface control agent. Its PB block is of the same origin as non-polar oils such as waste cooking oil and industrial heat transfer oil, which helps to achieve molecular-level compatibility with multi-source oil systems, making the regenerator system more homogeneous and stable, and reducing the risk of stratification caused by polarity differences when blending multi-source oils. The PS block contains an aromatic ring structure, which has a π-π stacking interaction with the aromatic rings of asphaltenes in aged asphalt. This helps to anchor the recycled material to the surface of aged asphalt, forming a pre-coated interface layer, so that the recycled material can maintain the interface integrity when mixed with new asphalt in the future. PGMA blocks contain epoxy groups, which undergo ring-opening chemical bonding with castor oil hydroxyl groups during the heating activation process. This helps to fix the interface control agent in the recycled material protective layer, reducing the risk of migration and deactivation under high temperature conditions, thereby extending the performance retention time of the recycled asphalt. PDMS blocks have low surface energy characteristics and tend to accumulate on the surface of the pre-coated layer to form a hydrophobic barrier layer, which helps to delay the penetration of water into the interior of the recycled asphalt, thereby reducing the probability of water damage. At the same time, PDMS segments themselves have a low glass transition temperature, which helps to improve the flexibility of the recycled asphalt under low temperature conditions and reduce the risk of low temperature cracking.

[0009] The functions of each block work together to form a stable and uniform pre-coating layer on the surface of aged asphalt, allowing the performance advantages of each oil component to be brought into play. The composite stabilizer is more evenly distributed in the homogeneous system constructed by the block copolymer, and the antioxidant efficiency is correspondingly improved. Ultimately, the recycled asphalt achieves a more balanced improvement in terms of high and low temperature resistance, water damage resistance, and aging resistance.

[0010] This application describes a modified and activated recycled asphalt prepared by using a PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer as an interface control agent. Under complex service environments such as high temperature and heavy load, low temperature freeze-thaw, and humid and rainy conditions, it helps to maintain the stability of road performance. It can improve the problems in the prior art where the system is prone to stratification when compounding multiple waste oils and it is difficult to balance the high and low temperature resistance and water damage resistance when regenerating a single oil.

[0011] In one specific feasible embodiment, the PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer is prepared by the following steps: S1-1 Under inert gas protection, 1,3-butadiene is dissolved in cyclohexane, n-butyllithium is added for polymerization, propylene oxide is added, and then 2-bromoisobutyryl bromide is added to react and obtain the macromolecular initiator PB-Br. S2-1 Under inert gas protection, the macromolecular initiator PB-Br, glycidyl methacrylate, cuprous bromide and pentamethyldiethylenetriamine obtained in step S1-1 are dissolved in anisole and reacted, and then post-treated to obtain PB-b-PGMA-Br. S3-1 Under inert gas protection, the PB-b-PGMA-Br, styrene, cuprous bromide and pentamethyldiethylenetriamine obtained in step S2-1 are dissolved in anisole and reacted, and then post-treated to obtain PB-b-PGMA-b-PS-Br. S4-1, PDMS-alkynyl group is prepared by reacting monoamine-terminated PDMS, propargyl acid, and condensing agent in dichloromethane; PB-b-PGMA-b-PS-Br and sodium azide obtained in step S3-1 are prepared by reacting in DMF to obtain PB-b-PGMA-b-PS-N3; under inert gas protection, PDMS-alkynyl group and PB-b-PGMA-b-PS-N3 are dissolved in DMF, and cuprous bromide and pentamethyldiethylenetriamine are added for reaction, followed by post-treatment to obtain PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer.

[0012] Experimental analysis revealed that the copolymer structure obtained through the above preparation steps is PB-b-PGMA-b-PS-b-PDMS. This ensures that the four blocks in the tetrablock copolymer are spatially ordered, preventing performance degradation due to steric hindrance and other factors. Simultaneously, the PB block, as an end-chain segment, exhibits good compatibility with non-polar oil systems, allowing it to preferentially distribute within the multi-source oil phase. This helps maintain the homogeneity and stability of the regenerator system and reduces the risk of stratification during multi-source oil blending. The PGMA block, located near the PB block end, undergoes ring-opening chemical bonding with castor oil hydroxyl groups during heating activation, anchoring the copolymer within the regenerated material protective layer and reducing the migration of the interface control agent under high-temperature conditions. The risk of deactivation is mitigated. The PS block, located near the PGMA end, extends its aromatic ring structure from the copolymer chain, facilitating π-π stacking interactions with the aromatic rings of asphaltenes in aged asphalt. This ensures interfacial integrity during subsequent mixing with new asphalt. Its adjacent distribution in the middle chain segment of the PGMA block further promotes bonding between the protective layer and asphalt, strengthening interfacial adhesion. The PDMS block, as the other end segment, possesses low surface energy and tends to accumulate on the surface of the pre-coated layer, forming a hydrophobic barrier layer that helps delay water penetration into the recycled asphalt. Simultaneously, the PDMS block itself has a low glass transition temperature, contributing to improved flexibility of the recycled asphalt under low-temperature conditions. Based on different interfacial affinities and spatial arrangements, these blocks act on the oil phase, castor oil hydroxyl sites, aged asphalt surface, and recycled asphalt surface, respectively, forming a well-coordinated multilayer interfacial structure. This results in a more balanced improvement in the recycled asphalt's resistance to high and low temperatures, water damage, and aging.

[0013] The inventors discovered through experiments that the segmental structure of polymers affects the final interfacial control. For example, PB-b-PS-b-PGMA-b-PDMS, as an interfacial control agent, deteriorates the anti-aging properties, water damage resistance, and storage stability of recycled asphalt. Analysis suggests this may be because the PDMS segments are close to the castor oil segments grafted onto PGMA, and are more prone to segment entanglement with multi-branched castor oil. On one hand, its migration behavior affects the migration of PGMA-grafted castor oil, leading to disordered oil distribution in the protective layer. The double bond structure of castor oil enriched on the surface exhibits deterioration in anti-aging properties under prolonged high temperatures. On the other hand, the branched and double bond structure of castor oil disrupts the close-packed characteristics of PDMS as a straight chain, thus affecting hydrophobic barrier properties.

[0014] In one specific implementation, the composite stabilizer includes an antioxidant, a metal passivator, and a high-boiling-point diluent.

[0015] In the above composite stabilizers, antioxidants are used to capture free radicals and decompose hydrogen peroxides, metal passivators are used to complex residual metal ions in industrial heat transfer oils to eliminate catalytic activity, and high-boiling-point diluents are used to increase the flash point of the composite stabilizer system and promote uniform dispersion of each component.

[0016] In one specific implementation, the antioxidant comprises antioxidant 1010 and an organically intercalated modified layered double hydroxide, the preparation steps of which are as follows: S1-2. Dissolve magnesium nitrate and aluminum nitrate in water, adjust the pH of the system to 8.5-10.5, and then perform hydrothermal crystallization. After post-treatment, a carbonate-type magnesium-aluminum layered bimetallic hydroxide precursor is obtained. S2-2. The carbonate-type magnesium-aluminum layered bimetallic hydroxide precursor obtained in step S1-2 and p-aminobenzoic acid are dispersed in water for ion exchange reaction, and then post-processed to obtain the organic intercalation modified layered bimetallic hydroxide.

[0017] More preferably, the weight ratio of the antioxidant 1010 to the organic intercalated modified layered bimetallic hydroxide is 1:(0.5-3).

[0018] The inventors discovered that antioxidant 1010, as a free radical scavenger, can effectively terminate the chain reaction during thermo-oxidative aging. However, it suffers from migration and volatilization issues in high-temperature asphalt systems, making it difficult to maintain its antioxidant effect for a long time. In contrast, organically intercalated modified layered bimetallic hydroxides (i.e., p-aminobenzoic acid intercalated magnesium-aluminum layered bimetallic hydroxides) are modified by p-aminobenzoic acid intercalation. The interlayer p-aminobenzoic acid anions can absorb ultraviolet light and convert it into heat energy. The layers themselves also function as physical barriers to oxygen and reflect ultraviolet light. Furthermore, the surface of the layers is rich in hydroxyl groups, exhibiting certain dispersibility and interfacial affinity in recycled material systems. However, when organically intercalated modified layered bimetallic hydroxides are added alone, their resistance to thermo-oxidative aging is limited, and they cannot replace the free radical scavenging function of hindered phenolic antioxidants.

[0019] The inventors further discovered that when antioxidant 1010 and organically intercalated modified layered bimetallic hydroxide are used in a weight ratio of 1:(0.5-3), they form a complementary antioxidant system: the organically intercalated modified layered bimetallic hydroxide layers physically block oxygen penetration into the recycled asphalt, while para-aminobenzoic acid absorbs ultraviolet light to reduce photo-oxidative aging; antioxidant 1010 captures already generated free radicals, inhibiting the spread of the oxidation chain reaction. Within this compounding ratio range, the synergistic antioxidant effect is better, and the antioxidant efficiency is significantly improved compared to the use of single components; if the proportion of antioxidant 1010 is too high, the physical barrier and ultraviolet absorption effects of the organically intercalated modified layered bimetallic hydroxide cannot be fully utilized; if the proportion of organically intercalated modified layered bimetallic hydroxide is too high, the free radical capture capacity in the system is insufficient, and the overall anti-thermal-oxidative aging effect decreases. Through the above compounding method, antioxidant 1010 and organic intercalated modified layered bimetallic hydroxide can form a synergy on different antioxidant mechanisms, so that the recycled asphalt can obtain a relatively balanced protective effect in terms of both thermo-oxidative aging and photo-oxidative aging.

[0020] In one specific feasible embodiment, the metal passivating agent is a long-chain alkane-epoxy group co-modified benzotriazole, and the preparation steps of the long-chain alkane-epoxy group co-modified benzotriazole are as follows: S1-3 Under inert gas protection, 1-hydroxybenzotriazole was dissolved in epichlorohydrin, and sodium hydroxide was added to react and obtain an epoxy-containing benzotriazole intermediate. S2-3. The epoxy-containing benzotriazole intermediate obtained in step S1-3 and butanol are added to toluene at a molar ratio of 1:(0.3-0.8), and tetrabutylammonium bromide is added to react. The reaction is then performed to obtain the long-chain alkane-epoxy co-modified benzotriazole.

[0021] During long-term high-temperature cycling, waste heat transfer oil retains metal shavings (such as iron and copper) generated by equipment wear. These metal ions catalyze oxidation reactions in the recycled asphalt system, accelerating the aging process of the asphalt. Benzotriazole and its derivatives, due to the lone pair electrons on their nitrogen atoms in their heterocycles, can form coordinate bonds with the empty orbitals of metal ions, thereby effectively complexing the metal ions and eliminating their catalytic activity, making them commonly used metal passivating agents. However, ordinary benzotriazole compounds have a small molecular structure, and when directly added to the regenerator system, they are prone to migration, volatilization, and loss during high-temperature asphalt mixing and construction, resulting in a lack of long-lasting metal passivation effects.

[0022] The inventors discovered that reacting 1-hydroxybenzotriazole with epichlorohydrin introduces epoxy groups into the benzotriazole molecule, yielding an epoxy-containing benzotriazole intermediate. This intermediate is then partially capped with butanol, causing the hydroxyl groups of butanol to undergo a ring-opening reaction with some of the epoxy groups. By controlling the molar ratio of the intermediate to butanol within the aforementioned range, a benzotriazole derivative retaining both partial epoxy and butyl end groups can be obtained. Under high-temperature shear conditions in the regenerator, the retained epoxy groups in this derivative can undergo ring-opening reactions with the epoxy groups of the PGMA block in the PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer and the hydroxyl groups in castor oil, forming chemical bonds. This anchors the metal passivator in the protective layer of the regenerated material, reducing the risk of migration and deactivation under high-temperature conditions. The butyl end group imparts a certain degree of lipophilicity to the derivative, aiding in its dispersion in non-polar oil phases such as waste edible oils and industrial heat transfer oils.

[0023] In one specific implementation, the high-boiling-point diluent is selected from one or more of aromatic oils, dioctyl phthalate, and dioctyl adipate.

[0024] Preferably, the high-boiling-point diluent comprises aromatic oil and dioctyl phthalate.

[0025] More preferably, the weight ratio of the aromatic oil to dioctyl phthalate is 1:(0.5-2).

[0026] While waste cooking oil and industrial heat transfer oil can replenish the light components and aromatics lost in aged asphalt, both types of oil experience a certain degree of volatility loss under high-temperature construction conditions. In particular, the low-boiling-point components remaining in industrial heat transfer oil are prone to volatilization and fumes during mixing, not only causing the loss of effective components but also affecting the construction environment and the consistency of recycled asphalt performance. Adding high-boiling-point diluents helps to raise the flash point of the entire recycling agent system and reduce volatility during high-temperature construction. However, a single type of high-boiling-point diluent cannot simultaneously meet the multiple requirements of dilution and viscosity reduction, compatibility with various oil components, and affinity with asphalt.

[0027] The inventors discovered that aromatic oils (such as rubber filler oils or extract oils rich in aromatic hydrocarbons) have good compatibility with asphalt and industrial heat transfer oils, replenishing the aromatic content in the system while helping to reduce the viscosity of multi-source oil blending systems and improve the wetting and penetration effect of recycling agents on the surface of aged asphalt. Dioctyl phthalate, as a high-boiling-point ester plasticizer, has both diluent-dispersing and plasticizing effects, helping to improve the low-temperature deformation capacity of recycled asphalt. When aromatic oils and dioctyl phthalate are blended in the above weight ratio, the two high-boiling-point diluents complement each other functionally: aromatic oils are more compatible with the asphalt and heat transfer oil system, enhancing the interfacial affinity between recycled materials and aged asphalt; dioctyl phthalate is more focused on improving the dispersion, fluidity, and low-temperature plasticizing effect of the system. The combination of the two helps to reduce the viscosity and volatility of the multi-source oil system without significantly adversely affecting the high-temperature performance of asphalt due to an excess of any one component.

[0028] If the weight ratio of aromatic oil to dioctyl phthalate exceeds 1:(0.5-2), the following may occur: If the proportion of aromatic oil is too high, the low-temperature plasticizing effect of the system will be insufficient, and the low-temperature crack resistance of the recycled asphalt may be affected; if the proportion of dioctyl phthalate is too high, the proportion of ester components in the system will be too large, which may lead to a significant decrease in the high-temperature viscosity of the recycled asphalt, thus weakening its rutting resistance. Therefore, controlling the weight ratio of aromatic oil to dioctyl phthalate within the range of 1:(0.5-2) helps to maintain the basic stability of the high-temperature performance of the recycled asphalt while simultaneously improving its workability and low-temperature performance.

[0029] Secondly, this application provides a method for preparing modified activated recycled asphalt based on multi-source waste oils, using the following technical solution: A method for preparing modified activated recycled asphalt based on multi-source waste oils includes the following steps: S1-4. Heat the waste cooking oil to 100-120℃ and keep it at that temperature to dehydrate until there are no bubbles. Add activated clay to degumme the oil and filter it to obtain pretreated waste cooking oil. After the industrial heat transfer oil is settled and impurities are removed, heat it to 110-130℃ and blow nitrogen to remove low-boiling substances to obtain pretreated industrial heat transfer oil. S2-4. Mix the interface control agent with castor oil and heat to 100-110℃ to react and form an interface control agent-castor oil pre-grafted product. S3-4. Mix the pretreated waste edible oil and the pretreated industrial heat transfer oil obtained in step S1-4, add the interface control agent - castor oil pregraft obtained in step S2-4, continue to stir evenly, heat to 115-125℃, add the composite stabilizer and stir to premix, continue to heat to 135-145℃ to react, and cool to room temperature to obtain the recycled material. S4-4. Add the recycled material to the aged asphalt at 2-6 wt% of the weight of the aged asphalt and stir to mix. Preheat to 140-150℃ for pre-coating to obtain modified activated recycled asphalt.

[0030] The modified activated recycled asphalt prepared by the above steps has a relatively uniform pre-coating layer. The multi-source oil components in this pre-coating layer are dispersed uniformly due to the oleophilic effect of the PB blocks of the tetrablock copolymer. The π-π stacking effect of the PS blocks facilitates the adhesion of the recycled material to the surface of aged asphalt. The chemical bonding between the PGMA blocks and castor oil fixes the copolymer in the pre-coating layer. The low surface energy of the PDMS blocks causes them to migrate to the surface, forming a hydrophobic barrier layer. During the subsequent mixing and heating activation process with the base asphalt, the multiple anchoring effects of the tetrablock copolymer ensure that the recycled material is dispersed relatively uniformly in the base asphalt in the form of microparticles, avoiding localized compositional inhomogeneities caused by oil aggregation. This results in a more consistent road performance of the recycled asphalt at the macroscopic level.

[0031] During road construction and use, when the modified activated recycled asphalt is mixed with the base asphalt and heated for activation, the pre-coating layer softens moderately under heat. However, due to the multiple anchoring effects of the tetrablock copolymer, the pre-coating layer is firmly bonded to the surface of the aged asphalt. The hydrophobic enrichment layer formed by the PDMS blocks on the surface reduces the interfacial tension and improves the interfacial compatibility and wettability between the pre-coating layer and the base asphalt. This results in an enhanced interfacial anchoring effect when the modified activated recycled asphalt is mixed with the base asphalt. Consequently, during the service of the road surface, the base asphalt acts as a continuous phase to encapsulate the modified activated recycled asphalt particles. The two work together to bear loads and environmental effects due to the good interfacial bonding, which improves the recycled asphalt's resistance to high and low temperatures, water damage, and aging compared to existing technologies.

[0032] In summary, this application includes at least one of the following beneficial technical effects: 1. This application utilizes a PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer as an interface control agent. The PB blocks are compatible with waste edible oil and industrial heat transfer oil, reducing the risk of stratification. Through the orderly coordination of the block functions in the tetrablock copolymer, the high and low temperature resistance, water damage resistance, and aging resistance of the recycled asphalt are improved in a more balanced manner.

[0033] 2. This application uses antioxidant 1010 and organically intercalated modified layered bimetallic hydroxide in a weight ratio of 1:0.5-1:3 as antioxidant components, so that the two components form a synergy in terms of antioxidant mechanism. Based on different antioxidant mechanisms, the two work together to achieve a relatively balanced protective effect on recycled asphalt in terms of both thermo-oxidative aging and photo-oxidative aging.

[0034] 3. This application uses benzotriazole co-modified with long-chain alkane-epoxy group as a metal passivator, anchoring the metal passivator in the protective layer of recycled material, reducing the risk of migration and deactivation under high temperature conditions, and enabling the metal passivator to play a more durable role in recycled asphalt.

[0035] 4. This application uses aromatic oil and dioctyl phthalate in a weight ratio of 1:0.5-1:2 as a high-boiling-point diluent, achieving functional complementarity: aromatic oil is compatible with asphalt and heat transfer oil systems, enhancing the interfacial affinity between recycled and aged asphalt; dioctyl phthalate reduces system viscosity, improving dispersion flowability and low-temperature plasticizing effect. The combination of these two components allows for a certain degree of control over the viscosity and volatility of the recycling agent system, improving workability and low-temperature performance to some extent while maintaining the basic stability of the high-temperature performance of recycled asphalt. Detailed Implementation

[0036] The present application will be further described in detail below with reference to embodiments and comparative examples: Some of the raw materials used in the examples and comparative examples: Monoamine-terminated PDMS, MW 3500, was purchased from Henan Qinpeng Technology Co., Ltd. The waste cooking oil used in this application is recycled catering waste oil, and solid impurities have been removed by filtration. Its moisture and impurities are both below 1 wt%, and its rotational viscosity and density are 0.048 Pa•s (60℃) and 0.93 g / cm³, respectively. 3 Furthermore, the acid value of the waste edible oil used in this application was determined in accordance with GB5009.229-2016 "National Food Safety Standard - Determination of Acid Value in Food", and the result was 30.24 mg KOH / g.

[0037] The industrial heat transfer oil used in this application is waste heat transfer oil that has been used in industrial heat transfer systems for a long time at high temperatures and is now scrapped. It has undergone sedimentation and impurity removal treatment before use. Its flash point is ≥180℃ and its acid value is ≤2mgKOH / g (refer to GB / T 7304 Determination of Acid Value of Petroleum Products).

[0038] The castor oil used in this application is industrial grade 1 refined castor oil, which meets the requirements of GB / T 8234-2009 "Castor Seed Oil" standard, and its hydroxyl value is ≥160mgKOH / g.

[0039] The aged asphalt used in this application is 70% grade from Hunan Baoli Asphalt Co., Ltd. #Petroleum asphalt aged after 8 years of service on the road surface. The penetration (25℃, 100g, 5s) / (0.1mm) of the aged asphalt material was measured by the T0604 test standard as 21.4, the ductility (15℃, 5cm / min) / cm was measured by the T0605 test standard as 3.0, and the softening point (ring and ball method) / ℃ was measured by the T0606 test standard as 63.0.

[0040] Rubber extraction oil, item number: SDL2025, CAS: 64742-95-6, product category: aromatic rubber oil, purchased from Hengshui Shuangdeli Chemical Co., Ltd.

[0041] Unless otherwise specified, all raw materials used in the examples and comparative examples are commercially available products.

[0042] Preparation Example 1 The preparation of the PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer is as follows: S1-1 Under nitrogen protection, 100 g of 1,3-butadiene was dissolved in 1000 mL of cyclohexane, and 1.42 mL of n-butyllithium was added. The mixture was heated to 50 °C and reacted for 3 hours. Then, 3.7 mL of propylene oxide was added and the reaction was continued for 1 hour. Finally, 4.6 g of 2-bromoisobutyryl bromide and 2 g of triethylamine were added, and the mixture was reacted at 12 °C for 12 hours. After the reaction was completed, the reaction solution was filtered to remove the triethylamine salt, and then poured into 2000 mL of methanol to precipitate the product. The precipitate was filtered, washed three times with methanol, and dried under vacuum at 40 °C for 24 hours to obtain the macromolecular initiator PB-Br. S2-1 Under nitrogen protection, 54g of the macromolecular initiator PB-Br obtained in step S1-1, 2.84g of glycidyl methacrylate, 0.14g of cuprous bromide, and 0.17g of pentamethyldiethylenetriamine were dissolved in 200mL of anisole, and the mixture was heated to 75℃ and reacted for 6 hours. After the reaction was completed, the reaction solution was passed through a neutral alumina column to remove the copper salt catalyst. The solution was eluted with anisole, and the eluent was collected. The collected eluent was concentrated and poured into 2000mL of methanol to precipitate the precipitate. The precipitate was filtered, washed three times with methanol, and dried under vacuum at 40℃ for 24 hours to obtain PB-b-PGMA-Br. S3-1 Under nitrogen protection, 56.8 g of PB-b-PGMA-Br obtained in step S2-1, 8.32 g of styrene, 0.14 g of cuprous bromide, and 0.17 g of pentamethyldiethylenetriamine were dissolved in 200 mL of anisole, and the mixture was heated to 100 °C and reacted for 8 hours. After the reaction was completed, the reaction solution was passed through a neutral alumina column to remove the copper salt catalyst. The solution was eluted with anisole, and the eluent was collected. The collected eluent was concentrated and poured into 2000 mL of methanol to precipitate the precipitate. The precipitate was filtered, washed three times with methanol, and dried under vacuum at 40 °C for 24 hours to obtain PB-b-PGMA-b-PS-Br. S4-1: 30g of monoamine-terminated PDMS, 1.05g of propargyl acid, 2.87g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 0.12g of 4-dimethylaminopyridine were dissolved in 150mL of dichloromethane and reacted at 25℃ for 12 hours. After the reaction, the mixture was washed three times successively with 100mL of deionized water and 100mL of saturated sodium chloride solution. The organic phase was dried over anhydrous magnesium sulfate and filtered. The filtrate was rotary evaporated at 40℃ to remove dichloromethane, yielding PDMS-alkynyl. 65.1g of PB-b-PGMA-b-PS-Br obtained in step S3-1 and 0.65g of sodium azide were dissolved in 150mL of DMF and reacted at 60℃ for 24 hours. After the reaction was complete, the reaction solution was slowly poured into 2000 mL of water to precipitate, filtered, and the precipitate was washed three times with water and dried under vacuum at 40 °C for 24 hours to obtain PB-b-PGMA-b-PS-N3. Under nitrogen protection, 9 g of PDMS-alkynyl group and 65.1 g of PB-b-PGMA-b-PS-N3 were dissolved in 150 mL of DMF, and 0.14 g of cuprous bromide and 0.17 g of pentamethyldiethylenetriamine were added. The mixture was heated to 40 °C and reacted for 18 hours. The reaction solution was passed through a neutral alumina column to remove the copper salt catalyst, eluted with N,N-dimethylformamide, and the eluent was collected. The collected eluent was concentrated and slowly poured into 2000 mL of methanol to precipitate, filtered, and the precipitate was washed three times with methanol and dried under vacuum at 40 °C for 24 hours to obtain PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer.

[0043] Preparation Example 2 The only difference between Preparation Example 2 and Preparation Example 1 is that the block copolymer obtained in Preparation Example 2 has the PS block placed before the PGMA block, i.e., PB-b-PS-b-PGMA-b-PDMS. The preparation steps are as follows: S1-1 Under nitrogen protection, 100 g of 1,3-butadiene was dissolved in 1000 mL of cyclohexane, and 1.42 mL of n-butyllithium was added. The mixture was heated to 50 °C and reacted for 3 hours. Then, 3.7 mL of propylene oxide was added and the reaction was continued for 1 hour. Finally, 4.6 g of 2-bromoisobutyryl bromide and 2 g of triethylamine were added, and the mixture was reacted at 12 °C for 12 hours. After the reaction was completed, the reaction solution was filtered to remove the triethylamine salt, and then poured into 2000 mL of methanol to precipitate the product. The precipitate was filtered, washed three times with methanol, and dried under vacuum at 40 °C for 24 hours to obtain the macromolecular initiator PB-Br. S2-1 Under nitrogen protection, 54g of the macromolecular initiator PB-Br obtained in step S1-1, 8.32g of styrene, 0.14g of cuprous bromide, and 0.17g of pentamethyldiethylenetriamine were dissolved in 200mL of anisole, and the mixture was heated to 100℃ and reacted for 8 hours. After the reaction was completed, the reaction solution was passed through a neutral alumina column to remove the copper salt catalyst. The solution was eluted with anisole, and the eluent was collected. The collected eluent was concentrated and poured into 2000mL of methanol to precipitate the precipitate. The precipitate was filtered, washed three times with methanol, and dried under vacuum at 40℃ for 24 hours to obtain PB-b-PS-Br. S3-1 Under nitrogen protection, 62.3 g of PB-b-PS-Br obtained in step S2-1, 2.84 g of glycidyl methacrylate, 0.14 g of cuprous bromide, and 0.17 g of pentamethyldiethylenetriamine were dissolved in 200 mL of anisole, and the mixture was heated to 75 °C and reacted for 6 hours. After the reaction was completed, the reaction solution was passed through a neutral alumina column to remove the copper salt catalyst. The solution was eluted with anisole, and the eluent was collected. The collected eluent was concentrated and poured into 2000 mL of methanol to precipitate the precipitate. The precipitate was filtered, washed three times with methanol, and dried under vacuum at 40 °C for 24 hours to obtain PB-b-PS-b-PGMA-Br. S4-1: Dissolve 65.1g of PB-b-PS-b-PGMA-Br obtained in step S3-1 and 0.65g of sodium azide in 150mL of N,N-dimethylformamide, and react at 60℃ for 24 hours. After the reaction is complete, slowly pour the reaction solution into 2000mL of water to precipitate, filter, wash the precipitate three times with water, and dry it under vacuum at 40℃ for 24 hours to obtain PB-b-PS-b-PGMA-N3; Dissolve 30g of monoamine-terminated PDMS, 1.05g of propargyl acid, 2.87g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 0.12g of 4-dimethylaminopyridine in 150mL of dichloromethane, and react at 25℃ for 12 hours. After the reaction, the product was washed three times successively with 100 mL of deionized water and 100 mL of saturated sodium chloride solution. The organic phase was dried over anhydrous magnesium sulfate and filtered. The filtrate was rotary evaporated at 40 °C to remove dichloromethane, yielding PDMS-alkynyl. Under nitrogen protection, 9 g of PDMS-alkynyl and 65.1 g of PB-b-PS-b-PGMA-N3 were dissolved in 150 mL of N,N-dimethylformamide. 0.14 g of cuprous bromide and 0.17 g of pentamethyldiethylenetriamine were added, and the mixture was heated to 40 °C and reacted for 18 hours. After the reaction, the reaction solution was passed through a neutral alumina column to remove the copper salt catalyst. The product was eluted with N,N-dimethylformamide, and the eluent was collected. The collected eluent was concentrated and slowly poured into 2000 mL of methanol to precipitate the product. The precipitate was filtered, washed three times with methanol, and dried under vacuum at 40 °C for 24 hours to obtain the PB-b-PS-b-PGMA-b-PDMS tetrablock copolymer.

[0044] Preparation Example 3 The preparation of organically intercalated modified layered bimetallic hydroxides is as follows: S1-2. Dissolve 100g magnesium nitrate and 73.15g aluminum nitrate in 780mL of water. Adjust the pH of the system to 9 using 2mol / L sodium hydroxide solution, and then heat to 115℃ for hydrothermal crystallization for 12 hours. After the reaction is complete, centrifuge to separate the precipitate, wash the precipitate with water until neutral, and dry it under vacuum at 80℃ for 12 hours to obtain a carbonate-type magnesium-aluminum layered bimetallic hydroxide precursor. S2-2. Disperse 30g of the carbonate-type magnesium-aluminum layered bimetallic hydroxide precursor obtained in step S1-2 and 60g of p-aminobenzoic acid in 1000mL of water. Adjust the pH of the system to 4.5 with dilute nitric acid, and heat to 70℃ with stirring for 18 hours. After the reaction is complete, centrifuge and wash the precipitate three times with water and ethanol respectively. Dry it under vacuum at 60℃ for 18 hours to obtain the organic intercalation modified layered bimetallic hydroxide.

[0045] Preparation Example 4 The preparation of benzotriazole co-modified with long-chain alkane-epoxy groups is as follows: S1-3 Under nitrogen protection, 100g of 1-hydroxybenzotriazole was dissolved in 550mL of epichlorohydrin. 44.4g of sodium hydroxide was added in nine equal portions, with a 15-minute interval between each portion. The mixture was heated to 60℃ and stirred for 8 hours. After the reaction was complete, the sodium chloride precipitate was removed by filtration, and excess epichlorohydrin was recovered by rotary evaporation to obtain an epoxy-containing benzotriazole intermediate. S2-3. 136 g (0.74 mol) of the epoxy-containing benzotriazole intermediate obtained in step S1-3, 27.4 g (0.37 mol) of butanol were added to 500 mL of toluene, followed by 0.74 g of tetrabutylammonium bromide. The mixture was heated to 110 °C and refluxed for 12 hours. After the reaction was complete, the mixture was washed three times successively with deionized water and saturated sodium chloride solution. The organic phase was dried over anhydrous magnesium sulfate, filtered, and toluene was removed by rotary evaporation to obtain long-chain alkane-epoxy-modified benzotriazole. Example Example 1

[0046] The preparation of modified activated recycled asphalt is as follows: S1-4. Heat the waste cooking oil to 110℃ and keep it at that temperature to dehydrate until there are no bubbles. Add activated clay to degumme the oil and filter it to obtain pretreated waste cooking oil. After the industrial heat transfer oil is settled and impurities are removed, heat it to 120℃ and blow nitrogen to remove low-boiling substances to obtain pretreated industrial heat transfer oil. S2-4. Mix 3 parts by weight of the PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer prepared in Example 1 with 10 parts by weight of castor oil, heat to 105°C and react for 2 hours to form an interface control agent-castor oil pregraft. S3-4. Mix 40 parts by weight of the pretreated waste edible oil obtained in step S1-4 and 30 parts by weight of the pretreated industrial heat transfer oil, add the interface control agent - castor oil pregraft obtained in step S2-4, continue to stir evenly, heat to 120°C, add 1.25 parts by weight of composite stabilizer (composite stabilizer includes 0.2 parts by weight of antioxidant 1010, 0.25 parts by weight of organic intercalation modified layered bimetallic hydroxide obtained in preparation example 3, 0.15 parts by weight of long-chain alkane-epoxy co-modified benzotriazole obtained in preparation example 4, 0.35 parts by weight of rubber extract oil, and 0.3 parts by weight of dioctyl phthalate), stir and premix for 30 minutes, continue to heat to 140°C and react for 1 hour, cool to room temperature to obtain recycled material; S4-4. Add 4 wt% of the recycled material to the aged asphalt and mix. Preheat to 145℃ and pre-coat for 30 minutes to obtain modified activated recycled asphalt. Example 2

[0047] The difference between Example 2 and Example 1 is that in steps S3-4 of Example 2, 0.2 parts by weight of antioxidant 1010 and 0.25 parts by weight of the organic intercalation modified layered bimetallic hydroxide prepared in Preparation Example 3 are replaced with 0.45 parts by weight of antioxidant 1010. Example 3

[0048] The difference between Example 3 and Example 1 is that in steps S3-4 of Example 3, 0.2 parts by weight of antioxidant 1010 and 0.25 parts by weight of the organic intercalation modified layered bimetallic hydroxide prepared in Example 3 are replaced with 0.45 parts by weight of the organic intercalation modified layered bimetallic hydroxide prepared in Example 3. Example 4

[0049] The difference between Example 4 and Example 1 is that in steps S3-4 of Example 4, 0.2 parts by weight of antioxidant 1010 and 0.25 parts by weight of the organic intercalation modified layered bimetallic hydroxide prepared in Preparation Example 3 are replaced with 0.4 parts by weight of antioxidant 1010 and 0.05 parts by weight of the organic intercalation modified layered bimetallic hydroxide prepared in Preparation Example 3. Example 5

[0050] The difference between Example 5 and Example 1 is that in steps S3-4 of Example 5, 0.2 parts by weight of antioxidant 1010 and 0.25 parts by weight of the organic intercalation modified layered bimetallic hydroxide prepared in Preparation Example 3 are replaced with 0.05 parts by weight of antioxidant 1010 and 0.4 parts by weight of the organic intercalation modified layered bimetallic hydroxide prepared in Preparation Example 3. Example 6

[0051] The difference between Example 6 and Example 1 is that in steps S3-4 of Example 6, 0.15 parts by weight of the long-chain alkane-epoxy co-modified benzotriazole obtained in Example 5 is replaced by an equal amount of 0.15 parts by weight of benzotriazole. Example 7

[0052] The difference between Example 7 and Example 1 is that in steps S3-4 of Example 7, 0.35 parts by weight of rubber extract oil and 0.3 parts by weight of dioctyl phthalate are replaced with 0.65 parts by weight of rubber extract oil. Example 8

[0053] The difference between Example 8 and Example 1 is that in step S3-4 of Example 8, 0.35 parts by weight of rubber extract oil and 0.3 parts by weight of dioctyl phthalate are replaced with 0.65 parts by weight of dioctyl phthalate. Example 9

[0054] The difference between Example 9 and Example 1 is that in step S3-4 of Example 9, 0.35 parts by weight of rubber extract oil and 0.3 parts by weight of dioctyl phthalate are replaced with 0.15 parts by weight of rubber extract oil and 0.5 parts by weight of dioctyl phthalate. Example 10

[0055] The difference between Example 10 and Example 1 is that in step S3-4 of Example 10, 0.35 parts by weight of rubber extract oil and 0.3 parts by weight of dioctyl phthalate are replaced with 0.5 parts by weight of rubber extract oil and 0.15 parts by weight of dioctyl phthalate.

[0056] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that, in steps S2-4 of Comparative Example 1, 3 parts by weight of the PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer prepared in Preparation Example 1 are replaced with 3 parts by weight of the PB-b-PS-b-PGMA-b-PDMS tetrablock copolymer prepared in Preparation Example 2.

[0057] The modified activated recycled asphalt prepared in each embodiment and comparative example was used as asphalt samples, and its performance was tested according to the following standards: (1) Basic physical performance test According to the specifications T0604, T0606, and T0605 of the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20), the penetration, softening point (ring and ball method), and ductility at 15℃ of each asphalt sample were determined. The test data are summarized in Table 1 below: Table 1. Basic physical property test data of each asphalt sample

[0058] (2) Anti-aging performance test According to the specifications in T0610 of the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20), the Rotating Thin Film Oven Test (RTFOT) was adopted. 35g of each asphalt sample was placed in a sample container and aged for 85 minutes at 163℃, an air flow rate of 4000mL / min, and a turntable speed of 15r / min. After aging, the mass change, residual penetration ratio, and residual ductility were measured. The test data are summarized in Table 2 below: Table 2. Test data on the anti-aging properties of each asphalt sample

[0059] (3) Water damage resistance test According to the provisions of T0729 in the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20), the freeze-thaw splitting test method is adopted to evaluate the water damage resistance of asphalt mixtures by measuring the splitting strength ratio (TSR) of specimens before and after freeze-thaw cycles. The test data are summarized in Table 3 below: Table 3. Test data on water damage resistance of each asphalt sample

[0060] (4) High-temperature performance test According to the provisions of T0719 in the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20), the dynamic stability of asphalt mixtures was determined using the rutting test method under a standard test temperature of 60℃ and a standard load of 780N. The test data are summarized in Table 4 below: Table 4. High-temperature performance test data of each asphalt sample

[0061] (5) Low temperature performance test According to the specifications in Section T0627 of the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20), the creep stiffness and creep rate of asphalt samples were determined using the bending beam rheometer (BBR) test method under a set temperature of -22℃. The test data are summarized in Table 5 below: Table 5. Low-temperature performance test data of each asphalt sample

[0062] Based on Examples 1-10 and Tables 1-5, it can be seen that Example 1 has the best overall performance. This may be because, although antioxidant 1010 alone can effectively inhibit thermo-oxidative aging, its low-temperature ductility loss is significant and its low-temperature crack resistance is seriously insufficient; although layered bimetallic hydroxide alone can improve water damage resistance and low-temperature ductility, its high-temperature performance is severely degraded; although the simple combination of the two has some improvement, its various properties are still inferior to those of Example 1; especially when the ratio of antioxidant 1010 to layered bimetallic hydroxide deviates from 1:(0.5-3), both high-temperature performance and anti-aging performance decrease to varying degrees, thus demonstrating the effect of the 1:(0.5-3) ratio.

[0063] The epoxy groups in benzotriazole derivatives achieve permanent anchoring of the stabilizer through chemical bonding. If replaced with ordinary benzotriazole, the anti-aging and anti-water damage properties decrease significantly, demonstrating the key role of the epoxy group chemical anchoring mechanism.

[0064] Rubber extract oil, acting as a high-boiling-point diluent carrier, ensures uniform dispersion of all components, while dioctyl phthalate acts as a plasticizer to improve low-temperature crack resistance. However, when rubber extract oil is used alone, it can be seen that the modified activated asphalt in the comparison exhibits insufficient low-temperature ductility and high-temperature performance; when dioctyl phthalate is used alone, although the low-temperature performance is excellent, the high-temperature performance is severely inadequate; when the ratio of the two deviates from the range of 1:(0.5-2), it is difficult to achieve the comprehensive high and low temperature balance effect of Example 1.

[0065] When antioxidant 1010, organic intercalated modified layered bimetallic hydroxide, long-chain alkane-epoxy co-modified benzotriazole, rubber extract oil, and dioctyl phthalate are used in combination at a weight ratio of 0.20:0.25:0.15:0.35:0.30, a significant synergistic effect is achieved among the five components, thereby realizing the comprehensive performance goals of "fully restoring basic physical properties, significantly enhancing anti-aging properties, improving water damage resistance, achieving balanced and excellent high and low temperature performance, and good storage stability".

[0066] Combining Example 1 and Comparative Example 1, and referring to Tables 1-5, it can be seen that the basic physical properties, anti-aging properties, water damage resistance, and low-temperature properties of Comparative Example 1 (with the interface control agent replaced by PB-b-PS-b-PGMA-b-PDMS) are all lower than those of Example 1; indicating that the present application can significantly improve the high and low temperature resistance, water damage resistance, and anti-aging properties of aged asphalt through the segment distribution design of the interface control agent.

[0067] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A modified and activated recycled asphalt based on multi-source waste oils, characterized in that, The material includes aged asphalt and recycled material pre-coated on the aged asphalt. The recycled material comprises the following components in parts by weight: 30-50 parts waste edible oil, 20-40 parts industrial heat transfer oil, 5-15 parts castor oil, 1-5 parts interface control agent, and 0.5-2 parts composite stabilizer. The interface control agent is a PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer.

2. The modified activated recycled asphalt based on multi-source waste oils according to claim 1, characterized in that, The PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer was prepared by the following steps: S1-1 Under inert gas protection, 1,3-butadiene is dissolved in cyclohexane, n-butyllithium is added for polymerization, propylene oxide is added, and then 2-bromoisobutyryl bromide is added to react and obtain the macromolecular initiator PB-Br. S2-1 Under inert gas protection, the macromolecular initiator PB-Br, glycidyl methacrylate, cuprous bromide and pentamethyldiethylenetriamine obtained in step S1-1 are dissolved in anisole and reacted, and then post-treated to obtain PB-b-PGMA-Br. S3-1 Under inert gas protection, the PB-b-PGMA-Br, styrene, cuprous bromide and pentamethyldiethylenetriamine obtained in step S2-1 are dissolved in anisole and reacted, and then post-treated to obtain PB-b-PGMA-b-PS-Br. S4-1, PDMS-alkynyl group is prepared by reacting monoamine-terminated PDMS, propargyl acid, and condensing agent in dichloromethane; PB-b-PGMA-b-PS-Br and sodium azide prepared in step S3-1 are prepared by reacting in DMF to obtain PB-b-PGMA-b-PS-N3; under inert gas protection, PDMS-alkynyl group and PB-b-PGMA-b-PS-N3 are dissolved in DMF, and cuprous bromide and pentamethyldiethylenetriamine are added for reaction, followed by post-treatment to obtain PB-b-PGMA-b-PS-b-PDMS tetrablock copolymer.

3. The modified activated recycled asphalt based on multi-source waste oils according to claim 1, characterized in that, The composite stabilizer includes antioxidants, metal passivators, and high-boiling-point diluents.

4. The modified activated recycled asphalt based on multi-source waste oils according to claim 3, characterized in that, The antioxidants include antioxidant 1010 and an organic intercalation-modified layered bimetallic hydroxide.

5. The modified activated recycled asphalt based on multi-source waste oils according to claim 4, characterized in that, The weight ratio of antioxidant 1010 to organic intercalation modified layered bimetallic hydroxide is 1:(0.5-3).

6. The modified activated recycled asphalt based on multi-source waste oils according to claim 3, characterized in that, The metal passivating agent is a long-chain alkane-epoxy group co-modified benzotriazole, and the preparation steps of the long-chain alkane-epoxy group co-modified benzotriazole are as follows: S1-3 Under inert gas protection, 1-hydroxybenzotriazole was dissolved in epichlorohydrin, and sodium hydroxide was added to react and obtain an epoxy-containing benzotriazole intermediate. S2-3. The epoxy-containing benzotriazole intermediate obtained in step S1-3 and butanol are added to toluene at a molar ratio of 1:(0.3-0.8), and tetrabutylammonium bromide is added to react. The reaction is then performed to obtain the long-chain alkane-epoxy co-modified benzotriazole.

7. The modified activated recycled asphalt based on multi-source waste oils according to claim 3, characterized in that, The high-boiling-point diluent is selected from one or more of aromatic oils, dioctyl phthalate, and dioctyl adipate.

8. The modified activated recycled asphalt based on multi-source waste oils according to claim 7, characterized in that, The high-boiling-point diluent includes aromatic oil and dioctyl phthalate.

9. The modified activated recycled asphalt based on multi-source waste oils according to claim 8, characterized in that, The weight ratio of the aromatic oil to dioctyl phthalate is 1:(0.5-2).

10. A method for preparing modified activated recycled asphalt based on multi-source waste oils as described in any one of claims 1-9, characterized in that, Includes the following steps: S1-4. Heat the waste cooking oil to 100-120℃ and keep it at that temperature to dehydrate until there are no bubbles. Add activated clay to degumme the oil and filter it to obtain pretreated waste cooking oil. After the industrial heat transfer oil is settled and impurities are removed, heat it to 110-130℃ and blow nitrogen to remove low-boiling substances to obtain pretreated industrial heat transfer oil. S2-4. Mix the interface control agent with castor oil and heat to 100-110℃ to react and form an interface control agent-castor oil pre-grafted product. S3-4. Mix the pretreated waste edible oil and the pretreated industrial heat transfer oil obtained in step S1-4, add the interface control agent - castor oil pregraft obtained in step S2-4, continue to stir evenly, heat to 115-125℃, add the composite stabilizer and stir to premix, continue to heat to 135-145℃ to react, and cool to room temperature to obtain the recycled material. S4-4. Add the recycled material to the aged asphalt at 2-6 wt% of the weight of the aged asphalt and stir to mix. Preheat to 140-150℃ for pre-coating to obtain modified activated recycled asphalt.